The formation of the conceptual foundations of pragma-dialectics in the second half of the 20th century: J. L. Austin, J. R. Searle and G. P. Grice - Sarycheva, Anna V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article reveals the conceptual foundations of pragma-dialectics, the formation of which is associated with the development of the theories of speech acts by J. L. Austin and J. R. Searle, as well as the concept of speech communication by G. P. Grice. The role of the theory of J. L. Austin who revealed the activity nature of statements, the conditions of their success and made a classification of speech acts, which was reflected in the modeling of pragmatic moves and the formulation of the meta-theoretical principles of pragma-dialectics, was substantiated. The significance of the theory of J. R. Searle, who made the analysis of illocutionary speech acts, interaction rules and revision of J. L. Austin’s classification, which influenced the formation of pragmatic and normative aspects in pragma-dialectics, has been revealed. The significance of the concept of G. P. Grice in the formation of conceptual foundations, including the principles and postulates of communication and communicative implicatures, which allows to build a rational interaction in the pragma-dialectics is revealed.
Keywords: analysis of ordinary language; classification of speech acts; illocutionary speech act; rules of interaction by J. R. Searle; communication postulates of G. P. Grice; communicative implicatures of G. P. Grice